The relationship between REITs industry characteristics and project performance: The moderating role of macroeconomic fluctuations - CAI, Ying (Institutional Knowledge at Singapore Management University, 2023)
As a distinct investment vehicle, Publicly Listed Real Estate Investment Trusts (REITs) projects enable real estate projects to be listed on the stock market. This study begins with the industry attributes of the underlying assets of Publicly Listed REITs projects. Using econometric methods, it analyzes the variances in market performance between growth and defensive REITs, based on annual data from 1,674 REITs products in the United States from 2005 to 2022 and 27 listed REITs in China from Q3 2021 to Q1 2023. The study also leverages the data from China to explore the moderating effects of macroeconomic factors such as interest rates, inflation, and stock market volatility on these relationships. In this research, the underlying assets of Publicly Listed REITs are categorized into growth and defensive types. Growth assets refer to investment targets with developmental potential, marked by high risk and high returns. In contrast, defensive assets imply investment in stable and reliable assets, usually backed by national policies and government subsidies. Empirical results indicate that growth REITs outperform defensive REITs regarding net profit and earnings per share but are associated with greater market volatility. Additionally, the study uncovers the negative moderating effect of interest rates on the profitability of growth REITs, suggesting their earning capacities might be constrained in high-interest-rate environments. In contrast, the impacts of inflation and stock market volatility on the performance of REITs are not significant. This research provides practical implications for investors on effectively allocating assets between growth and defensive REITs, emphasizing the importance of making investment choices based on individual risk preferences and market conditions. Simultaneously, it offers insights for policymakers on utilizing REITs as a financing channel for urbanization and infrastructure development. Despite its valuable insights, this study has limitations, including the constraints of data, not fully considering all factors that could affect the performance of REITs, and the limited sample period. Future research could expand in these areas to achieve a more comprehensive and deeper understanding of the REITs market.